2022
DOI: 10.1007/s43681-022-00163-7
|View full text |Cite
|
Sign up to set email alerts
|

AI-deploying organizations are key to addressing ‘perfect storm’ of AI risks

Abstract: We argue that a perfect storm of five conditions heightens the risk of harm to society from artificial intelligence: (1) the powerful, invisible nature of AI, (2) low public awareness and AI literacy, (3) rapid scaled deployment of AI, (4) insufficient regulation, and (5) the gap between trustworthy AI principles and practices. To prevent harm, fit-for-purpose regulation and public AI literacy programs have been recommended, but education and government regulation will not be sufficient: AI-deploying organizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…In the digital age, modern society is experiencing unprecedented changes, with Artificial Intelligence (AI) playing a pivotal role in these transformations. The increasing importance of AI in the digitalization trend of contemporary society is evident, as its development profoundly influences various fields, from daily life to industrial innovation (Curtis et al 2022). Global companies, such as Google, Apple, and Tesla, are investing substantial resources in AI research and development, introducing innovative products and services to the market.…”
Section: Introductionmentioning
confidence: 99%
“…In the digital age, modern society is experiencing unprecedented changes, with Artificial Intelligence (AI) playing a pivotal role in these transformations. The increasing importance of AI in the digitalization trend of contemporary society is evident, as its development profoundly influences various fields, from daily life to industrial innovation (Curtis et al 2022). Global companies, such as Google, Apple, and Tesla, are investing substantial resources in AI research and development, introducing innovative products and services to the market.…”
Section: Introductionmentioning
confidence: 99%
“…(Yudkowsky, 2008), based on previous results (Buiten, 2019), this study has shown that, effective regulation of the activities of AI, to mitigate its effect on human jobs could improve the regulation of AI ethics in the workplace . The practical significance of this study is that, it suggests the need for AI deploying firms to address its workforce on; the attendant risk of deploying AI, supposed standards, and AI ethical requirement in the workplace (Caitlin, et. al, 2022).…”
Section: Research Resultsmentioning
confidence: 99%
“…The regulation of AI should include defining what constitutes "unsafe" AI and determining what aspects of AI should be subject to regulation [74]. This requires a clear understanding of the anticipated risks and benefits of AI technologies on a global scale as well as insights into the public's trust and the acceptance of AI systems.…”
Section: The Balance Between the Benefits And Harms Of Ai Chatbotsmentioning
confidence: 99%